2021
DOI: 10.1093/asj/sjab397
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Plastic Surgery Outcomes: A Systematic Review and Meta-analysis

Abstract: Background Obesity is a potential risk factor for complications in plastic surgeries. However, the data presented by primary studies are contradictory. Objectives The aim of this study was to summarize and clarify the divergences in the literature to provide a better understanding of the impact of obesity in different plastic surgery procedures. Methods We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 109 publications
1
21
1
Order By: Relevance
“…Furthermore, breast hypertrophy and asymmetry have an increased incidence in patients with higher BMI, 28 potentially leading to greater breast-related physical concerns preoperatively. On the other hand, the positive influence of both BMI and resected weight on postoperative satisfaction with breasts is supported by evidence from the autologous breast reconstruction and body contouring literature, which report comparable postoperative satisfaction of obese patients compared with nonobese counterparts 29–31 . Most importantly, our analysis demonstrated a lack of correlation between average BMI and the average change in BREAST-Q scores across any of the QoL domains.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, breast hypertrophy and asymmetry have an increased incidence in patients with higher BMI, 28 potentially leading to greater breast-related physical concerns preoperatively. On the other hand, the positive influence of both BMI and resected weight on postoperative satisfaction with breasts is supported by evidence from the autologous breast reconstruction and body contouring literature, which report comparable postoperative satisfaction of obese patients compared with nonobese counterparts 29–31 . Most importantly, our analysis demonstrated a lack of correlation between average BMI and the average change in BREAST-Q scores across any of the QoL domains.…”
Section: Discussionsupporting
confidence: 65%
“…79,80,82 Instead, clinical judgment should account for the combination of procedures to be performed, procedure indication, and the overall health of the patient. 80–82…”
Section: Periprocedural Safety Principlesmentioning
confidence: 99%
“…51,75,82–85 Similarly, specific to liposuction, a lipoaspirate volume less than 5 L was considered safe. 82 Two recent reviews found an increased risk of VTE in those with a lipoaspirate more than 3 L, 85 and an increased risk of VTE and other complications in those with a lipoaspirate more than 3.5 L. 86 Therefore, further postoperative monitoring can be considered for patients with a BMI more than 30 kg/m 2 , liposuction volume more than 3 L, operative time more than 4 hours, and those undergoing combined procedures. 51,85 Postoperative monitoring must be supervised by a health care provider with documentation of a course of events.…”
Section: Periprocedural Safety Principlesmentioning
confidence: 99%
See 2 more Smart Citations